Mitochondria biogenesis and the development of diabetic retinopathy - dos Santos, Julia M. (2011)
Retinal mitochondria become dysfunctional and their DNA (mtDNA) is damaged in diabetes. Biogenesis of mitochondria DNA is tightly controlled by nuclear-mitochondrial transcriptional factors, and translocation of transcription factor A (TFAM) to the mitochondria is essential for transcription and replication. Our aim is to investigate the effect of diabetes on nuclear-mitochondrial communication in the retina, and its role in the development of retinopathy. Damage of mtDNA, copy number and biogenesis (PGC1, NRF1, TFAM) were analyzed in the retina from streptozotocin-diabetic wildtype (WT) and MnSOD transgenic (Tg) mice. Binding between TFAM and chaperone Hsp70 was quantified by co-immunoprecipitation. The key parameters were confirmed in isolated retinal endothelial cells, and in the retina from human donors with diabetic retinopathy. Diabetes in WT mice increased retinal mtDNA damage, and decreased copy number. The gene transcripts of PGC1, NRF1 and TFAM were increased, but mitochondrial accumulation of TFAM was significantly decreased, and the binding of Hsp70 and TFAM was subnormal compared to WT-non diabetic mice. However, Tg-diabetic mice were protected from retinal mtDNA damage, and alterations in mitochondrial biogenesis. In retinal endothelial cells, high glucose decreased the number of mitochondria, as demonstrated by MitoTracker green staining and by electron microscopy, and impaired the transcriptional factors. Similar alterations in biogenesis were observed in the donors with diabetic retinopathy. Thus, retinal mitochondria biogenesis is under the control of superoxide radicals, and is impaired in diabetes, possibly by decreased transport of TFAM to the mitochondria. Modulation of biogenesis by pharmaceutical or molecular means may provide a potential strategy to retard the development/progression of diabetic retinopathy.